Pendampingan Perencanaan Keuangan UMKM : Menyusun Modal, Laba Dan Belanja Usaha Desa Suka Sari Kecamatan Kabawetan Kabupaten Kepahiang - M. Reza Oktananda; Dwi Sinta; Puspa Rini; Novriza Wahyu Ardiansyah; Marchela Dwi Agustin (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving economic growth and improving community welfare, particularly in rural areas. However, many rural MSME actors still face challenges in financial planning and management, including inaccurate calculation of capital and profit, unstructured business expenditure planning, and the absence of separation between personal and business finances. This community service program aimed to enhance the financial literacy and financial planning skills of MSME actors in Suka Sari Village, Kabawetan District, Kepahiang Regency. The program was implemented through several stages, including preliminary observation to identify key financial management issues, interactive counseling on basic business finance concepts, simulation of capital and profit calculations, and hands-on practice in simple financial record-keeping using an easily applicable format. The results of the program indicate a significant improvement in participants’ understanding of business capital and profit calculation, their ability to plan business expenditures more systematically, and increased awareness of the importance of separating personal and business finances. This study demonstrates that participatory and practice-based financial assistance is effective in fostering simple financial management habits, which can support the sustainability and long-term development of MSMEs in rural communities.